Theoretical Research Aspects of the Behaviour of the Insured and their Manifestations in the Lithuanian Life Assurance Market - Kindurys, Vytautas (Ekonomika, 2008)
The research problems of the behaviour of the insured are topical issues for both theory and practice. From the theoretical paint of view, the disclosure of behaviour of the insured and a comparative analysis of various authors’ opinions on the behaviour research make it possible to define the contents and sequence of the research of such a phenomenon. On the one hand, the practical aspect of such research in the Lithuanian life assurance market may help insurance companies to determine the needs and expectations of the insured and also the possibilities of applying definite methods and means that could change the behaviour of the insured in the market of life assurance services and induce their interest in insurance products. It is also important to note that Lithuanian life assurance companies do not give enough attention to thorough and complex researches of the behaviour of the insured. Furthermore, the theoretical and practical problems of the behaviour of the insured are not discussed in the Lithuanian scientific economic literature. On the other hand, the problem of the behaviour of the insured in scientific literature of western countries is also slightly overlooked. This problem has been mainly analysed not as a complex but in its separate aspects, such as the quality of insurance services and the satisfaction of the insured with these services, interrelations between insurers and the insured, and so on. Therefore, to reveal the theoretical questions of the behaviour of the insured in the life assurance market, works of different authors dealing with the behaviour of consumers of other services or of financial services have been used.While evaluating the external and internal factors influencing the behaviour of the insured, it is necessary to divide this rather sophisticated research into the following stages: the behaviour of the insured before acquiring assurance (reasons for obtaining assurance, the perceptible image of insurance companies and their evaluation criteria, confidence while deciding to acquire assurance, attitude towards information sources); the behaviour of the insured in the course of assurance (insurance distribution channels, the number of insurance events, evaluation criteria of the received insurance services); the behaviour of the insured after signing the assurance police (meeting the requirements of the insured, satisfaction of the insured with the insurer, loyalty of the insured, change of the insurance company).According to the experience of western insurance companies, the choice of insurers and insurance products depends on the cultural background and sophistication of the insured, the main purpose of obtaining an insurance product, the actual income of the insured, the external environment (including various social factors). Moreover, according to researches of western insurance companies, the behaviour of the insured is directly related to social changes of contemporary society (i.e. of the social and cultural environment), such as changes of standards of living, lifestyle, etc. in the latter years.Analysis of the results revealed the following behaviour peculiarities of the Lithuanian life assurance clients: 40% of the respondents have life assurance polices; more than half of these intend to obtain other life assurance products in future; the most frequently mentioned criteria while choosing life assurance services are tax deductions and increasing income; accumulative life assurance is the most popular of all life assurance kinds and the respondents are satisfied with its services; the majority of the respondents (60%) that have no life assurance would like to have it in future; while choosing life assurance services, the insured pay more attention to the reliability of assurance companies and to the professionalism of insurance agents; 25% of the respondents are ready for long-term saving and would definitely entrust their insurance matters to professionals.